Identification of cables insulator degradation using partial discharge and fuzzy logic technique / Ahmad Syahril Mohd Nawawi - Mohd Nawawi, Ahmad Syahril (2004)
This paper described a new technique to identify insulator's cable condition using ultrasonic sensor and fuzzy logic. Ultrasonic sensor produced the signal that can indicate the level of degradation of cable insulator. Then the signal is transferred to the personal computer (PC) by using the computer microphone. The transferred signal then being stored Matrix Laboratory (MATLAB) workspace folder for further analysis. The application of Discrete Wavelet Transform (DWT) is used to extract the feature of the ultrasonic signal. Finally, the Fuzzy Logic (FL) from MATLAB simulation software is being proposed as a classification to differentiate between normal cable and fault cable. FL is capable to classify the signal by developing and appropriate rule and function.